Invasive Scedosporium spp. and Lomentospora prolificans infections in pediatric patients: Analysis of 55 cases from FungiScope® and the literature. (March 2020) - Seidel, Danila; Hassler, Angela; Salmanton-García, Jon; Koehler, Philipp; Mellinghoff, Sibylle C.; Carlesse, Fabianne; Cheng, Matthew P.; Falces-Romero, Iker; Herbrecht, Raoul; Jover Sáenz, Alfredo; Klimko, Nikolai; Mareş, Mihai; et al.
Highlights: Similar mortality for Scedosporium and Lomentospora -related infections in children. Median time to death for children with Lomentospora -infections was less than a week. Infection of the brain and blood were associated with high mortality. Voriconazole administration and surgery for antifungal treatment improve survival. Abstract: Objectives: Current knowledge on infections caused by Scedosporium spp. and Lomentospora prolificans in children is scarce. We therefore aim to provide an overview of risk groups, clinical manifestation and treatment strategies of these infections. Methods: Pediatric patients (age ≤18 years) with proven/probable Scedosporium spp. or L. prolificans infection were identified in PubMed and the FungiScope® registry. Data on diagnosis, treatment and outcome were collected. Results: Fifty-five children (median age 9 years [IQR: 5–14]) with invasive Scedosporium spp. (n = 33) or L. prolificans (n = 22) infection were identified between 1990 and 2019. Malignancy, trauma and near drowning were the most common risk factors. Infections were frequently disseminated. Most patients received systemic antifungal therapy, mainly voriconazole and amphotericin B, plus surgical treatment. Overall, day 42 mortality was 31%, higher for L. prolificans (50%) compared to Scedosporium spp. (18%). L. prolificans infection was associated with a shorter median survival time compared to Scedosporium spp. (6 days [IQR: 3–28] versus 61 days [IQR: 16–148]). Treatment for malignancy and severe disseminated infection were associated with particularly poor outcome (HR 8.33 [95% CI 1.35–51.40] and HR 6.12 [95% CI 1.52–24.66], respectively). Voriconazole use at any time and surgery for antifungal treatment were associated with improved clinical outcome (HR 0.33 [95% CI 0.11–0.99] and HR 0.09 [95% CI 0.02–0.40], respectively). Conclusions: Scedosporium spp. and L. prolificans infections in children are associated with high mortality despite comprehensive antifungal therapy. Voriconazole usage and surgical intervention are associated with successful outcome.